2022
DOI: 10.1371/journal.pgph.0000288
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of short birth interval in Bangladesh: Evidence from the linked data of population and health facility survey

Abstract: The Sustainable Development Goals 3 targets significant reductions in maternal and under-five deaths by 2030. The prevalence of these deaths is significantly associated with short birth intervals (SBI). Identification of factors associated with SBI is pivotal for intervening with appropriate programmes to reduce occurrence of SBI and associated adverse consequences. This study aimed to determine the factors associated with SBI in Bangladesh. A total of 5,941 women included in the 2017/18 Bangladesh Demographic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…The prevalence of SBI among mothers who lost their index child was higher compared to women whose index child was alive for all EDHS years (2000–2016). This finding was consistent with evidence from studies conducted in Bangladesh ( 20 , 21 ) that found that the experience of a child dying at birth in a woman’s second recent pregnancy was a significant predictor of SBI. The mother’s education level significantly influenced the SBI of women.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of SBI among mothers who lost their index child was higher compared to women whose index child was alive for all EDHS years (2000–2016). This finding was consistent with evidence from studies conducted in Bangladesh ( 20 , 21 ) that found that the experience of a child dying at birth in a woman’s second recent pregnancy was a significant predictor of SBI. The mother’s education level significantly influenced the SBI of women.…”
Section: Discussionsupporting
confidence: 91%
“…Women who have information about short birth intervals through any media channel are expected to have a better understanding of the negative impact of short birth intervals on maternal and children's health. As a result, women who have no exposure to any media are more likely to experience short birth intervals than those who have media exposure 28,29 . Whereas all the zones in the country except North-west were associated with high odds of having a short birth interval at the national level and rural areas, only south-east and south-south were significantly associated with high odds of having short birth interval among urban residents.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the uptake of maternal and postnatal healthcare services are also key to the prevention of neonatal and infant mortality. Access to family planning services and use of contraception, including access to contraception at the post-partum period, should also be ensured, particularly among the disadvantaged and unaware population where occurrence of birth in short interval is very higher 16,42 . Existing health problems, including maternal undernutrition and anaemia, are required to be addressed properly.…”
Section: Discussionmentioning
confidence: 99%